Immunophenotype of the inflammatory response in the central and enteric nervous systems of cockatiels (Nymphicus hollandicus) experimentally infected with parrot bornavirus 2. Issue 3 (May 2022) - Leal de Araújo, Jeann; Rech, Raquel R.; Rodrigues-Hoffmann, Aline; Giaretta, Paula R.; Cirqueira, Cinthya; Wenceslau, Raphael Rocha; Tizard, Ian; Diaz-Delgado, Josué
Proventricular dilatation disease is a lethal disease of psittacine birds. In this study, we characterized the local cellular immune response in the brain, proventriculus, and small intestine of 27 cockatiels ( Nymphicus hollandicus ) experimentally infected with parrot bornavirus 2 (PaBV-2). Perivascular cuffs in the brain were composed of CD3+ T-lymphocytes and Iba1+ macrophages/microglia in most cockatiels (n = 26). In the ganglia of the proventriculus, CD3+ T-lymphocytes (n = 17) and Iba1+ macrophages (n = 13) prevailed. The ganglia of the small intestine had a more homogeneous distribution of these leukocytes, including PAX5+ B-lymphocytes (n = 9), CD3+ T-lymphocytes (n = 8), and Iba1+ macrophages (n = 8). Our results indicate that perivascular cuffs in the brain and the inflammatory infiltrate in the proventriculus of PaBV-2-infected cockatiels is predominately composed of T-lymphocytes, while the inflammatory infiltrates in the ganglia of the small intestine are characterized by a mixed infiltrate composed of T-lymphocytes, B-lymphocytes, and macrophages.